Food insecurity in households with persons with disabilities in a situation of extreme vulnerability in Brazil: A secondary cross-sectional analysisResearch in context - Ursula Viana Bagni; Alexia Vieira de Abreu Rodrigues; Eloah Costa de Sant’Anna Ribeiro; Rosana Salles-Costa; Aline Alves Ferreira (The Lancet Regional Health. Americas, 2023)
Summary: Background: Inequities in access to education, work and health care are striking among persons with disabilities, making this population more vulnerable to poverty, lack of access to basic services and violation of rights such as access to food. Household food insecurity (HFI), marked by precarious income, has increased among persons with disabilities. In Brazil, the Continuous Cash Benefit (In Portuguese, Benefício de Prestação Continuada - BPC) is the guarantee of a minimum wage for persons with disabilities as a measure to promote social security and access to income in a situation of extreme poverty. Thus, the objective of this study was to assess HFI among persons with disabilities in extreme poverty in Brazil. Methods: A cross-sectional study with national representation was carried out with data from the 2017/2018 Family Budget Survey, with moderate and severe food insecurity as the dependent variable, and the situation of food insecurity measured using the Brazilian Food Insecurity Scale. Prevalence and odds ratio estimates were generated with 99% confidence intervals. Findings: Approximately 25% of households experienced HFI, with a higher prevalence in the North Region (41%), receiving up to 1 income quintile (36.6%), with a female (26.2%) and black person (31%) as a reference. The analysis model found that region, per capita household income, and social benefits received in the household were statistically significant factors. Interpretation: The BPC proved to be an important source of household income for persons with disabilities living in extreme poverty in Brazil: in almost three-quarters of the households, it was the only social benefit received, and, for most of them, it represented more than half of the total household income. Funding: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.